Secure Text Conferencing System Using Multiple Layer Encryptions - Boskany, Najmadin Wahid (Sulaimani Journal for Pure and Applied Sciences, 2013)
The coding theory becomes increasingly important over the decades. There are some different works that have been dedicated to the problems of cryptography. In the present paper, the design and implementation of a secure text conferencing system have been proposed and implemented. Also explained how plaintext can be encrypted in three levels before sending it to the destination has been explained. Later, how ciphered text decrypted from destination side to its origin plaintext has been described.
Keywords: Secure Text Conferencing; Plaintext; Cipher Text; Promiscuous Mode; Windows Sockets; Network Security; ClientServer Network